1992
DOI: 10.1113/jphysiol.1992.sp019430
|View full text |Cite
|
Sign up to set email alerts
|

Discharge characteristics and rapid resetting of autoactive aortic baroreceptors in rats.

Abstract: SUMMARY1. An in vitro aortic arch-aortic nerve preparation was used to characterize the pressure-discharge properties of aortic 'autoactive' baroreceptors (aBRs), a functionally unique group of baroreceptors that discharge continuously below pressure threshold (Pth). These units contrast to more familiar 'quiescent' BRs (qBRs) that are silent below Pth. This study also examined whether aBRs rapidly reset to sustained changes in mean arterial pressure (MAP), and whether they respond to local vasoconstriction, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

1994
1994
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…It has been proposed that the two types of fibers may act differentially, having different "purposes," allowing arterial pressure to be buffered over a wide operating range and both rapid and slow changes in arterial pressure to be buffered (84). Importantly, there is evidence that the two fiber types may differ in their ability to reset (69,85). It should also be noted that the typical methods for monitoring afferent baroreceptor activity, namely single or so-called whole nerve recordings, are biased toward A fibers with their larger spikes (1, 6), despite the fact that histological studies have shown that C fibers outnumber A fibers in baroreceptor nerves in both the rabbit (79) and rat (7).…”
Section: Possible Mechanisms Regulating the Long-term Level Of Sna: Amentioning
confidence: 99%
“…It has been proposed that the two types of fibers may act differentially, having different "purposes," allowing arterial pressure to be buffered over a wide operating range and both rapid and slow changes in arterial pressure to be buffered (84). Importantly, there is evidence that the two fiber types may differ in their ability to reset (69,85). It should also be noted that the typical methods for monitoring afferent baroreceptor activity, namely single or so-called whole nerve recordings, are biased toward A fibers with their larger spikes (1, 6), despite the fact that histological studies have shown that C fibers outnumber A fibers in baroreceptor nerves in both the rabbit (79) and rat (7).…”
Section: Possible Mechanisms Regulating the Long-term Level Of Sna: Amentioning
confidence: 99%
“…While the presence of activity in aortic baroreceptors at low pressures has been reported previously [2,3,11], there is no report that has quantified or explained this behaviour at low pressure. We have now demonstrated that approximately one-third of the aortic baroreceptors in the rabbit have a non-monotonic J-shaped response curve.…”
Section: Discussionmentioning
confidence: 78%
“…Thus the J-shaped multifibre response curve may be attributable, at least in part, to the behaviour of a substantial subpopulation of aortic baroreceptors within the ADN [13]. Indeed, there are limited reports of fibres possessing these appropriate firing characteristics [2,3,11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…16 In the present study, we recorded the whole nerve activity during natural pulsatile pressure and observed a sigmoidal-shaped curve for the MAP-aortic nerve activity relation. We therefore plotted aortic nerve activity at 5-mm Hg intervals of MAP and fitted the data to a logistic function curve 14 ' 15 by using a nonlinear regression program (PROC NUN, SAS Institute Inc) on a computer (PS/2 model 50Z, IBM Co).…”
mentioning
confidence: 58%